Heterogeneous Recognition of beta 2-glycoprotein I by Antibodies from Antiphospholipid Syndrome Patients - Guerin, J.; Sim, R.; Yu, B-B.; Ferluga, J.; Feighery, C.; Jackson, J. (Thrombosis and Haemostasis, 2000)
Beta 2-glycoprotein I plays a pivotal role in the binding of antiphospholipid antibodies to phospholipid in patients with antiphospholipid syndrome. In this study the nature of the epitopes on beta 2-glycoprotein I (β2-GPI) recognised by sera from antiphospholipid syndrome (APS) patients (n = 15) was investigated and compared to rabbit polyclonal and mouse monoclonal anti-β2-GPI antibodies. β2-GPI was only recognised when bound to a high affinity binding support. The antigenic epitope on β2-GPI recognised by all APS patients was also dependent on disulphide bond integrity. Digestion of β2-GPI with elastase rapidly destroyed the epitope(s) on β2-GPI recognised by antibodies in 91% of APS patients. The main cleavage occurred at tryptophan316-lysine317 in the fifth domain. Digestion with staphylococcal V8 protease resulted in a 50% reduction in antibody binding in 81% of patients and the cleavage sites mainly involved the first domain of the molecule. There was considerable variability in the recognition of six different species of β2-GPI by serum from APS patients. The epitopes on β2-GPI bound by APS sera appear conformationally determined in all patients but are quite heterogeneous in the regions of β2-GPI that are recognised.
Keywords: Beta 2-glycoprotein I; antibodies; antiphospholipid syndrome; heterogeneity; species